IBNU MISKAWAIH DAN PEMIKIRANNYA TENTANG PENDIDIKAN (Analisis terhadap Konsep Pendidikan Akhlak dalam Kitab Tahzib al-Akhlaq wa Tathhir al-A’raq) - Dr. Afifuddin Harisah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
In this article the author examines the important thinking of one of the scholars, thinkers and renowned Muslim philosophers, namely Ibn Miskawayh, particularly in the field of education and morals contained in the book of essay Tahzib al-Akhlaq wa al-A'raq Tathhir. This study is library research to focus research on the conception and writing in his book Ibn Miskawayh it. In his view, education is essentially and should aim to create human character and noble character. To achieve these objectives, taking into account the possibility of human education and individual differences in the psychological state of learners, Ibn Miskawayh suggests natural methods (thariqah thabi'iyyah) in education. The main idea of ​​the natural methods offered Ibn Miskawaihi this is that the implementation of the educational work should be based on the development of the inner and outer man. Because the needs and conditions of physio-psychological aspects become very urgent.